Inhibition of Alpha-Amylase and Antioxidant Activities of Fractions from The Methanol Extracts of The Stem of Allanblackia floribunda Oliv [Guttiferae] - Ayoola, G. A.; Akinwole , A. A.; Okoye, E. I.; Johnson , O. O.; Akpanika , G. A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Allanblackia floribunda Oliv. (Guttiferae) is a tree from the tropical rain forest that has been of tremendous benefit in traditional medicine for decades all over Africa. In this study, the antioxidant and hypoglycaemic potential of fractions from the methanol extract of the stem of Allanblackia floribunda were investigated. The antioxidant activity was investigated by determining DPPH (1,1-dipenyl-2-picryl hydrazyl) radical scavenging activities and the hypoglycaemic potential was investigated using the ?-amylase inhibitory method. All the fractions except the ethyl acetate fraction had potent free radical scavenging activities against DPPH. Chloroform and water fractions were the most active. IC50 values of 10.75, 90.15, 91.34 and >100 ?g/ml were obtained for Vitamin C, chloroform, water and n-hexane fractions respectively. Alpha amylase inhibition experiment was carried out at concentration of extracts ranging from 50-2000?g/ml. At 2000 ?g/ml, Acarbose had 46.04% inhibition of ?-amylase while n-hexane, chloroform, ethyl acetate, water fractions had highest inhibitory activities of 45.6, 56.53, 67.00, 72.74% respectively at this concentration. Acarbose had its highest inhibitory activity of 71.4% at 200 ?g/ml while all the fractions had highest activity at 2000 ?g/ml. The polar fractions were more active compared to the non-polar fractions at inhibiting ?-amylase, hence, it is desirable to investigate the bioactive constituents present in the water and ethyl acetate fractions in pursuit of potential anti-diabetic agents.